2006
DOI: 10.1111/j.1442-2042.2006.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary macromolecules and renal tubular cell protection from oxalate injury: Comparison of normal subjects and recurrent stone formers

Abstract: Aim:To determine whether urinary macromolecules (UMM), which are the high molecular weight substances in urine, can provide protection against the oxalate-associated injury to the renal tubular cells. Methods: UMM were extracted from 24-h urine of 12 healthy adult male volunteers and 13 recurrent-stone-former male patients. Urine parameters in relation to urolithiasis were measured, including the level of glycosaminoglycans (GAG) in the UMM. MadinDarby canine kidney (MDCK) cells were used to evaluate the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
(61 reference statements)
0
6
0
1
Order By: Relevance
“…Earlier studies have elucidated the abrasive effects of both oxalate and CaOx crystals in renal epithelial cell injury through free radicals 22 , 23 . ROS generation increases in response to renin angiotensin system activation and eventually causes mitochondrial damage 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have elucidated the abrasive effects of both oxalate and CaOx crystals in renal epithelial cell injury through free radicals 22 , 23 . ROS generation increases in response to renin angiotensin system activation and eventually causes mitochondrial damage 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Urinary macromolecules (UMM) might protect renal tubular cells from oxalate‐related injury, and UMM from normal subjects might have a stronger protective effect than UMM from stone‐forming subjects 76 …”
Section: Renal Tubular Cell Injury and Its Inhibitorsmentioning
confidence: 99%
“…75 Urinary macromolecules (UMM) might protect renal tubular cells from oxalate-related injury, and UMM from normal subjects might have a stronger protective effect than UMM from stone-forming subjects. 76 Fibronectin is one of the macromolecules oversecreted from renal tubular cells as a result of stimulation by COM crystals. 20 It has also been reported that FN protected against renal tubular cell injury caused by oxalate and COM crystals, as shown by MTT [3-(4,5dimethylthiazol-2-yl)-2,5-diphenyl-tetrazoliumbromide] assay and morphological examination.…”
Section: Renal Tubular Cell Injury and Its Inhibitorsmentioning
confidence: 99%
“…may predispose individuals to stone formation. 35 GAGs have been shown to be present on all surfaces of the urinary tract and to directly inhibit stone formation. [36][37][38] The amount of GAGs excreted in urine and the integrity of the GAG layer in various parts of the urinary tract may be involved in the adhesion, formation, and growth of urine crystals.…”
Section: Urinary Gags In Kidney Diseasesmentioning
confidence: 99%
“…42 Although various inhibitory effects of GAGs on stone formation were identified in several in vitro studies, the results of studies comparing urinary GAG levels in patients and control groups are contradictory. 13,35,39,[43][44][45] Many reports showed low urinary GAGs in adult nephrolithiasis patients. 38,39,43,[45][46][47][48] Ombra et al 48 separated the patients into subgroups and found a significant difference in the urinary GAG/creatinine ratio between the recurrent stone disease patients and the first-time stone disease patients.…”
Section: Urinary Gags In Kidney Diseasesmentioning
confidence: 99%